Evaluation of the Divine Proportion in the facial profile of young females - Jahanbin Arezoo; Basafa Mohammad; Alizadeh Yekta (Indian Journal of Dental Research, 2008)
Background: Beauty is the phenomenon of experiencing pleasure, through the perception of balance. According to some authors, attractive faces have ideal proportions that are related to the Divine Proportion (1.618:1). Aim: The purpose of this study was to evaluate the Divine Proportion in the human profile and investigate the effects of this ratio on the perception of the beauty of the profile. Study and Design: We conducted a cross-sectional study to determine the mentioned aims. Materials and Methods : In this cross-sectional study, fifty females in the age range of 20-25 years, with acceptable profiles were selected. Standardized profile silhouettes were each given a score by 20 judges (consisting of 10 men and 10 women) using the visual analog scale. Five landmarks were determined and five ratios were measured on the silhouettes by using the adobe photoshop program. Statistical Analysis: The Student′s t test was used to compare profile proportions of the subjects. Results: Statistical analysis showed none of the proportions had the mean of 1.618, but in subjects having higher esthetic scores, trichion (Te)-soft tissue menton (Me):Tr-subnasale (Sn) and Tr-Me:soft tissue nasion (N)-Me, with the mean of 1.58 were closer to Divine Proportion. Conclusions : The results suggested the perception of beauty is influenced by the Divine Proportions and Tr-Me:Tr-Sn and Tr-Me:N-Me are the most influential ratios in the perception of the beauty of profile; however, if the Divine Proportion is to be used in treatment planning, it should be used along with other factors.